Eigenfrequecy-based damage identification method for non-destructive testing based on topology optimization. Issue 3 (4th March 2017) - Nishizu, T.; Takezawa, A.; Kitamura, M.
ABSTRACT: Non-destructive testing (NDT) detects damage according to a difference in a physical phenomenon between a normal structure and damaged structure. As a solution avoiding human errors in NDT, a numerical method based on a dynamical numerical analysis model and a structural optimization algorithm was proposed. This method automatically derives a structure with a response that is equal to that of a damaged structure through an optimization procedure. Among structural optimization methods, topology optimization can optimize the structure fundamentally by changing the topology and not just the shape of a structure. Thus, topology optimization is employed together with eigenfrequency analysis, which is the most fundamental methodology of NDT. The proposed method derives a structure that has the same eigenfrequencies as a damaged structure employing topology optimization. The shape and location of damage can be identified through the optimal shape obtained.